Effectiveness, safety, and practicality of intramuscular progesterone in restoring pregnancy outcomes during frozen embryo transfers - Nguyen, Chien Ngoc; Nguyen, Trang Thi Nhu; Le, Thanh Thien; Vu, Phuong Bich; Le, Lan Thi Phuong; Pham, Nha Ba; To, Huong Minh; Nguyen, Xuyen Thi; Nguyen, Ly Thi Tam; Nguyen, Van Thi Cam; Pham, Yen Thi Kim; Tran, Tran Hue; et al. (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate whether progesterone (P4) supplementation in patients with low serum progesterone levels after normal luteal phase support (LPS) improves pregnancy outcomes in women undergoing frozen embryo transfer (FET).MethodsA retrospective, single-center cohort study including 1301 vitrified-warmed frozen embryo transfer (FET) cycles conducted from May 2021 to July 2023 at Vinmec Times City International Hospital. A total of 696 FET cycles from individual patients were analyzed for pregnancy outcome. Patients with serum P4 level ≥ 10 ng/ml (Normal P4, n=359) continued to receive standard LPS, while those with P4 levels < 10 ng/ml (Rescue P4, n=337) received 50 mg intramuscular P4 injection daily in addition to the standard LPS for 7–10 days.ResultsDaily intramuscular P4 effectively restored serum P4 levels to that of the Normal P4 group and resulted in pregnancy outcome comparable to that of patients with P4 levels ≥10 ng/ml. Notably, the efficacy of this protocol was consistent even in very low serum P4 concentrations (< 4ng/ml) and was independent of preimplantation genetic testing for aneuploidy (PGT-A).ConclusionIntramuscular P4 effectively increased serum P4 levels resulting in pregnancy and neonatal outcomes comparable to those in patients with P4 levels ≥10 ng/ml. This approach provides a safe, effective intervention to improve FET outcomes, supporting the routine inclusion of serum P4 testing and intramuscular P4 rescue in standard FET protocols.